2011
DOI: 10.1002/ecj.10377
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically driven two‐axis optical beam steering MEMS mirror and its dependence of actuation on magnetic field

Abstract: SUMMARYThis paper describes the development of an electromagnetically driven two-axis MEMS mirror which steers an optical beam, and the dependence of the tilting angles on the magnet shape and size and the initial gap between planar coils and the magnet surface. A reflective Au mirror (1.8 × 1.8 mm 2 ) can be tilted bidirectionally with an electromagnetic force induced by the current of the planar coils and the magnetic field of a permanent magnet. A newly developed MEMS mirror device (10 × 10 × 0.2 mm 3 ) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Figure 16 shows a 3D OCT image of fingertip tissue where the fingerprint orientations are visible. Watanabe et al [56] have demonstrated an electromagnetic MEMS scanner for OCT imaging. The schematic diagram of a fabricated mirror scanner is shown in Figure 17.…”
Section: Examples Of Electromagnetic Oct Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 16 shows a 3D OCT image of fingertip tissue where the fingerprint orientations are visible. Watanabe et al [56] have demonstrated an electromagnetic MEMS scanner for OCT imaging. The schematic diagram of a fabricated mirror scanner is shown in Figure 17.…”
Section: Examples Of Electromagnetic Oct Probesmentioning
confidence: 99%
“…Two x-scan coils are formed on the x-frame. All the coils have a Watanabe et al [56] have demonstrated an electromagnetic MEMS scanner for OCT imaging. The schematic diagram of a fabricated mirror scanner is shown in Figure 17.…”
Section: Examples Of Electromagnetic Oct Probesmentioning
confidence: 99%
See 1 more Smart Citation